DISPENSASI NIKAH PASCA UNDANG-UNDANG NOMOR 16 TAHUN 2019 DAN IMPLIKASINYA TERHADAP PERKARA PERCERAIAN DI PENGADILAN AGAMA DEPOK - Rahma Shafira Yuniarta (2021)
This study aims to analyze the practice of marital dispensation after Law No. 16 of 2019 on Amendments to Law No. 1 of 1974 on Marriage and its implications for divorce rates in Depok religious courts. This type of research is juridical normative. The data source consists of primary and secondary. The data sources used in this study include Law No. 1 of 1974, Government Regulation No. 9 of 1975 on the regulation of the implementation of Law No. 1974 on Marriage, Presidential Instruction No. 1 of 1991 on Compilation of Islamic Law, and Law No. 16 of 2019 on Amendments to Law No. 1 of 1974 on Marriage. This study shows that the practice of underage marriage in depok religious courts with the change of marriage age limit through Law No. 16 of 2019 does not have a significant impact on the decrease in marriage dispensation applications in religious courts. Changes made by raising the age of marriage turned out not to be effective enough to cope with the decrease in child marriage rates. Thus, by itself also implies the potential for increasing divorce rates for the marriage of minors. The issue of marriage of minors is not only related to the dimensions of the legal structure, the substance of the law, but also related to the cultural problems of society and religiosity and religious understanding. Keywords: Marriage, Dispensation, Divorce.